Review About Various Satellite Image Segmentation - Shabir Ahmed Mir; T. Padma (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this paper, a review about different algorithm is proposed efficiently to segment the satellite images. Segmentation of Image is one of the promising and active researches in recent years. As literature prove that region segmentation will produce better results. Human visual perception is more effective than any machine vision systems for extracting semantic information from image. There are various segmentation techniques are available. Fuzzy C Means (FCM), Expectation Minimization (EM) and K-Means algorithm is developed to estimate parameters of the prior probabilities and likelihood probabilities. Finally Peak Signal to Noise Ratio (PSNR) is calculated for all the algorithms and reviewed.